2015
DOI: 10.1002/anie.201505452
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed SiOx/Al2O3 Catalysts Illuminate the Reactivity of Isolated Silanol Sites

Abstract: The reaction of γ-alumina with tetraethylorthosilicate (TEOS) vapor at low temperatures selectively yields monomeric SiO(x) species on the alumina surface. These isolated (-AlO)3Si(OH) sites are characterized by PXRD, XPS, DRIFTS of adsorbed NH3, CO, and pyridine, and (29)Si and (27)Al DNP-enhanced solid-state NMR spectroscopy. The formation of isolated sites suggests that TEOS reacts preferentially at strong Lewis acid sites on the γ-Al2O3 surface, functionalizing the surface with "mild" Brønsted acid sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 49 publications
4
61
0
Order By: Relevance
“…The maxima located at ∼280°C can be assigned to weak and medium strength acid sites [43]. Acid site concentration (Table 1) decreased with increasing modification time, similar to previous observations of selective consumption of the strong Al Lewis acid sites upon exposure to TEOS [44]. Pyridine adsorption followed by IR spectroscopy indicated that only Lewis acid sites (LAS) were present in the parent Pt/Al 2 O 3 catalyst (Fig.…”
Section: F Liu Et Alsupporting
confidence: 87%
See 2 more Smart Citations
“…The maxima located at ∼280°C can be assigned to weak and medium strength acid sites [43]. Acid site concentration (Table 1) decreased with increasing modification time, similar to previous observations of selective consumption of the strong Al Lewis acid sites upon exposure to TEOS [44]. Pyridine adsorption followed by IR spectroscopy indicated that only Lewis acid sites (LAS) were present in the parent Pt/Al 2 O 3 catalyst (Fig.…”
Section: F Liu Et Alsupporting
confidence: 87%
“…Given the change in catalyst acidity before and after modification, it can be inferred that Al-O-Si linkages were formed successfully at the expense of specific surface Lewis acid sites, which serve as original hydration sites for the undesired conversion to boehmite. Similarly, Mouat et al [44] suggested that TEOS modification of an γ-alumina surface preferentially occurs on strong Lewis acid sites, also observing the formation of "mild" Brønsted acid sites. As stated above, silica deposition was hypothesized to inhibit water adsorption of Al 2 O 3 by Al coordinative saturation of unsaturated Al species and the formation of AleOeSi bonds, with the characterization data now suggesting that improved stability under hydrothermal conditions can indeed be anticipated.…”
Section: F Liu Et Almentioning
confidence: 93%
See 1 more Smart Citation
“…[3] TheB rønsted acid sites are,h owever, recognized as being surface hydroxyls, which challenges their characterization by conventional SSNMR. [3] TheB rønsted acid sites are,h owever, recognized as being surface hydroxyls, which challenges their characterization by conventional SSNMR.…”
mentioning
confidence: 99%
“…17 And, the only presence of silica tetrahedron framework peak and surface silanols peak at 103.1 eV and 532.6 eV, respectively revealed no obvious bonding between MSN and the MoS2 nanoparticles. 18,19 SAXS pattern of UsMSND@MSN exhibited two resolved diffraction peaks with reciprocal spacing, 1/dhk, ratios of approximate 1:√3 ( Figure 2D). Together with the TEM results of MSN precursor ( Figure S3), this could be indexed as the typical (100) and (110) reflections of an ordered hexagonal P6mm mesostructure with unit cell parameter (a0) of 3.73 nm.…”
mentioning
confidence: 99%